Bark as Medicine: A Systematic Review of Pharmacological Properties and Therapeutic Benefits of Medicinal Plant Barks (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Plant bark, a multifaceted structure integral to the survival and function of woody plants, haslong been recognized for its diverse pharmacological properties. This systematic reviewcomprehensively explores the pharmacological effects and therapeutic potential of medicinal plantbarks. The structure and chemical composition of plant bark are elucidated, shedding light on theintricate layers and tissues that contribute to its protective functions, nutrient transport, andenvironmental interactions. The pharmacological exploration encompasses a myriad of bioactivecompounds found in plant barks, including alkaloids, phenols, tannins, flavonoids, terpenoids, andglycosides. The review synthesizes current knowledge on the major pharmacological activitiesassociated with plant barks, emphasizing their anti-inflammatory, antimicrobial, antioxidant, antidiabetic,and antitumor properties. The anti-inflammatory potential of certain plant barks, exemplified by WhiteWillow's salicin content, reveals promising avenues for addressing inflammatory conditions.Additionally, the antimicrobial efficacy of bark compounds, such as quinine from Cinchona trees andcinnamaldehyde from Cinnamon trees, positions them as valuable agents in combating infectiousdiseases. The antioxidant activity of phenolic-rich barks emerges as a crucial factor in mitigatingoxidative stress-related disorders, while select barks show antidiabetic effects, offering potentialinterventions for diabetes management. Furthermore, the review explores the burgeoning field ofresearch on plant barks with antitumor activity, presenting a promising frontier in the quest for novelanticancer agents.Throughout history, diverse cultures have harnessed the medicinal benefits of plant barks, and thisreview bridges traditional remedies with contemporary scientific understanding. The collective findingsunderscore the rich pharmacological diversity housed within medicinal plant barks, inviting furtherresearch and exploration of their therapeutic applications in modern medicine.